Requirements for strengthening the strategic leadership of academic leaders at private universities in Riyadh City - Abdelrazek, Magda Mostafa; Al-Shehri, Fawzia Abdullah; Al-Muihi, Basmaa Sudan (Journal of Educational and Psychological Sciences, 2021)
The study aimed to reveal the requirements for strengthening strategic leadership (human, organizational and material) among academic leaders in private universities in Riyadh, the researchers used the descriptive approach, and the study tool (questionnaire) was applied to faculty members in (Arab East Colleges, Al-Faisal University, and Yamama University In Riyadh, the sample size reached (80) faculty members. The study reached a number of results, the most important of which are The study members of the faculty members of the private universities agree with a high degree that one of the most important human requirements to enhance the strategic leadership of academic leaders is the following: (The leader’s ability to predict the future needs of the department - Department of the department in creative and creative ways), also that one of the most important organizational requirements to enhance leadership The strategy for academic leaders is the following: (making new adjustments in work methods from time to time - the commitment of the leaders to a vision that helps to distinguish when selecting faculty members - making sure that the work is going according to the specified plans), and the study recommended the importance of developing the leader's ability to predict the future The department needs, in order to manage the department in creative and creative ways.
Keywords: Strategic Leadership; Academic Leadership; Private Universities